2008
DOI: 10.1016/s1028-4559(08)60054-6
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of Fetal Abdominal Circumference in an Asian Population: Analysis of 50,131 Records

Abstract: To the best of our knowledge, our series is the largest sample of AC reported in the medical literature. We believe that the gestational age-specific nomogram of fetal AC is important for further clinical assessment of fetal growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Eighty‐three publications from 32 countries were identified; 14–96 the earliest was published in 1971 and the latest in 2008. In two publications, 49,76 multiple study designs were used, for instance AC using a longitudinal and a cross‐sectional design; the best described methodology with the highest quality score was used in the final analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighty‐three publications from 32 countries were identified; 14–96 the earliest was published in 1971 and the latest in 2008. In two publications, 49,76 multiple study designs were used, for instance AC using a longitudinal and a cross‐sectional design; the best described methodology with the highest quality score was used in the final analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, it is arbitrary and illogical to exclude from analysis the outer percentiles of the ultrasound measurement values. For instance, measurements greater than 1.66 or two standard deviations from the mean 31,64 may well represent physiological healthy variability. Similarly, exclusion of cases with birthweight in the outer percentiles has been used by some studies 80,91 in order to define normal growth.…”
Section: Discussionmentioning
confidence: 99%
“…with foetal anthropometric parameters. Morphological studies into umbilical cord structure have observed that umbilical cord in the face of foetal intrauterine growth restriction and hypertensive disorders with normal umbilical artery Doppler parameters exhibited reduced total vessel area and Wharton's jelly area in comparison with normal fetuses [15][16][17][18]. However, significant difference in the vein diameter was observed between the neonates of normotensive mothers and pregnancy induced hypertensive mothers respectively, with the PIHs having larger vein diameter.…”
Section: Discussionmentioning
confidence: 99%